2019
DOI: 10.1111/bju.14778
|View full text |Cite
|
Sign up to set email alerts
|

Teaching medical students digital rectal examination: a randomized study of simulated model vs rectal examination volunteers

Abstract: ConclusionThis study showed that teaching DRE with the assistance of volunteer patients improves inexperienced students' confidence in performing DRE, and the incorporation of such training should be considered in the DRE education programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…Additionally, in specific interviews with M aori men, Williams et al [23] addressed health system failure to consider cultural factors as a significant contributor to the reluctance among men to seek healthcare for prostate-related problems. DRE may be one of these factors because, in spite of the simplicity of the test, it could represent a source of distress to many men [24].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in specific interviews with M aori men, Williams et al [23] addressed health system failure to consider cultural factors as a significant contributor to the reluctance among men to seek healthcare for prostate-related problems. DRE may be one of these factors because, in spite of the simplicity of the test, it could represent a source of distress to many men [24].…”
Section: Discussionmentioning
confidence: 99%
“…Worryingly, senior medical students lack training in performing a DRE and up to 44% have never performed the examination on a human subject when graduating 17,18 . A randomized controlled study found that medical students that had practiced DRE on phantoms and human volunteers had an increased confidence in performing and trusting the results of the examination compared with students who only practiced on phantoms 19 . Like many other practical clinical skills, the DRE has a learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical examination should provide baseline information on the presence of deformity, the point of maximum curvature, presence/location/size of the plaque, penile length, and areas of tenderness. On examination, the penis should be stretched fully to assess the penile length and palpate for the presence of any penile plaque [15,16]. Digital photographs are often helpful and penile examination with the aid of vasoactive intracavernosal injection can be used to confirm and document the extent of penile curvature/deformity, vascular integrity and erectile response [16].…”
Section: Patient Evaluation and Diagnosis: Clinical Principle/ Expertmentioning
confidence: 99%